BIM demystified : an architect's guide to Building Information Modelling/Management (BIM). - Race, Steve (Architect) (Riba Publishing, 2013)
'BIM Demystified' is a short, practical introduction to Building Information Modelling (BIM). Addressing BIM from the point of view of mainstream practice as opposed to a cutting-edge technological perspective, it offers a user-friendly yet thorough explanation of a subject which is often swamped by jargon and deluged with spin.